2012
DOI: 10.1371/journal.pone.0032780
|View full text |Cite
|
Sign up to set email alerts
|

Benefits for Dominant Red Deer Hinds under a Competitive Feeding System: Food Access Behavior, Diet and Nutrient Selection

Abstract: Social dominance is widely known to facilitate access to food resources in many animal species such as deer. However, research has paid little attention to dominance in ad libitum access to food because it was thought not to result in any benefit for dominant individuals. In this study we assessed if, even under ad libitum conditions, social rank may allow dominant hinds to consume the preferred components of food. Forty-four red deer hinds (Cervus elaphus) were allowed to consume ad libitum meal consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 65 publications
1
39
0
Order By: Relevance
“…This demonstrates that although energy is generally recognized as important in food selection (Robbins ), we also need to pay attention to the sources of energy (i.e., fat, sugar, and protein). Relatively few studies have analyzed the fat content of ungulate food plants to date (Deguchi et al , Ceacero et al ), perhaps because most previous works have been conducted in areas where forage plants are typically low in crude fat. However, ungulates living in warmer habitats consume more fruits and seeds (Gayot et al , Soumya et al , Agetsuma et al ), which may have high fat content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates that although energy is generally recognized as important in food selection (Robbins ), we also need to pay attention to the sources of energy (i.e., fat, sugar, and protein). Relatively few studies have analyzed the fat content of ungulate food plants to date (Deguchi et al , Ceacero et al ), perhaps because most previous works have been conducted in areas where forage plants are typically low in crude fat. However, ungulates living in warmer habitats consume more fruits and seeds (Gayot et al , Soumya et al , Agetsuma et al ), which may have high fat content.…”
Section: Discussionmentioning
confidence: 99%
“…The results, however, have not always been as expected (Dostaler et al ). For example, researchers reported that ungulates selected food items with less soluble carbohydrates (Vourc'h et al , Ceacero et al ) and protein (Berteaux et al , Vourc'h et al , Verheyden‐Tixier et al , Ceacero et al , Zweifel‐Schielly et al ), and more structural carbohydrates (such as neutral detergent fiber and cellulose; Vourc'h et al , Verheyden‐Tixier et al , Ceacero et al ), lignin (Vourc'h et al , Verheyden‐Tixier et al ), and plant secondary metabolites (Tixier et al , Verheyden‐Tixier et al , Zweifel‐Schielly et al ), though this can vary with some conditions such as season or individual. It has been argued that these inconsistencies are related to characteristics of the ungulate digestive system (Verheyden‐Tixier et al ) or the influence of varying seasons (Van der Wal et al , Zweifel‐Schielly et al ).…”
mentioning
confidence: 99%
“…That means that diet protein is used for milk production with higher priority than for the immune system, especially under food restriction situations 11. Social rank determines the access to food in hinds, and allows them to select feed with a greater nutritional value 36. Thus, subordinate hinds may have less resources for immune barriers, being forced to use internal immunity (WBC; similar results were found in restricted feed experiments in the study by Landete-Castillejos and others37).…”
Section: Discussionmentioning
confidence: 74%
“…For example, dominant juvenile Atlantic salmon Salmo salar grew faster not because of a direct effect of their higher resting metabolism but because dominance allowed them to hold better feeding territories than subordinates (Reid et al 2011). Dominance is associated with preferential access to limited food sources and selection of higher energy forage in red deer (Appleby 1980;Thouless 1990;Ceacero et al 2012). A high resting heart rate (and probably resting metabolic rate) might reflect the increased maintenance costs of a physiological system that on average processes a higher rate of food energy than in subdominants (i.e., higher idling costs of a larger metabolic engine; Biro and Stamps 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Social rank among female red deer might positively affect winter survival by allowing dominant individuals to displace subordinate individuals from limited patches of high-quality foraging habitat (Appleby 1980;Thouless 1990;Ceacero et al 2012). Dominance is associated with increased fitness in female red deer on the Isle of Rum in Scotland (Clutton-Brock et al 1986;Wilson et al 2011).…”
Section: Social Dominance Is Associated With Individual Differences Imentioning
confidence: 99%